The Importance of the Role of Sports and Games in the System of Physical Education (Eurasian Research Bulletin, 2023)
In the article physical education of sports games in the system place and importance about word done _ Sports games features , sportc from sports games in training of practitioners health improve duties solution to do and to them sports propaganda their work take to go issues cover received